Prophylactic Intra-Peritoneal Drainage After Pancreatic Resection: An Updated Meta-Analysis - Liu, Xinxin; Chen, Kai; Chu, Xiangyu; Liu, Guangnian; Yang, Yinmo; Tian, Xiaodong (Frontiers in Oncology, 2021)
Introduction: Prophylactic intra-peritoneal drainage has been considered to be an effective measure to reduce postoperative complications after pancreatectomy. However, routinely placed drainage during abdominal surgery may be unnecessary or even harmful to some patients, due to the possibility of increasing complications. And there is still controversy about the prophylactic intra-peritoneal drainage after pancreatectomy. This meta-analysis aimed to analyze the incidence of complications after either pancreaticoduodenectomy (PD) or distal pancreatectomy (DP) in the drain group and no-drain group. Methods: Data were retrieved from four electronic databases PubMed, EMBASE, the Cochrane Library and Web of Science up to December 2020, including the outcomes of individual treatment after PD and DP, mortality, morbidity, clinically relevant postoperative pancreatic fistula (CR-POPF), bile leak, wound infection, postoperative hemorrhage, delayed gastric emptying (DGE), intra-abdominal abscess, reoperation, intervened radiology (IR), and readmission. Cochrane Collaboration Handbook and the criteria of the Newcastle-Ottawa scale were used to assess the quality of studies included. Results: We included 15 studies after strict screening. 13 studies with 16,648 patients were analyzed to assess the effect of drain placement on patients with different surgery procedures, and 4 studies with 6,990 patients were analyzed to assess the effect of drain placement on patients with different fistula risk. For patients undergoing PD, the drain group had lower mortality but higher rate of CR-POPF than the no-drain group. For patients undergoing DP, the drain group had higher rates of CR-POPF, wound infection and readmission. There were no significant differences in bile leak, hemorrhage, DGE, intra-abdominal abscess, and IR in either overall or each subgroup. For Low-risk subgroup, the rates of hemorrhage, DGE and morbidity were higher after drainage. For High-risk subgroup, the rate of hemorrhage was higher while the rates of reoperation and morbidity were lower in the drain group. Conclusions: Intraperitoneal drainage may benefit some patients undergoing PD, especially those with high pancreatic fistula risk. For DP, current evidences suggest that routine drainage might not benefit patients, but no clear conclusions can be drawn because of the study limitations. Keywords: intra-peritoneal drainage, pancreatic resection, pancreaticoduodenectomy, distal pancreatectomy, meta-analysis